Risk Factors and Outcomes Associated with Multidrug-Resistant Acinetobacter baumannii upon Intensive Care Unit Admission - Blanco, Natalia (Antimicrob Agents Chemother, 2017)
Multidrug-resistant (MDR) Acinetobacter baumannii, associated with broad-spectrum antibiotic use, is an important nosocomial pathogen associated with morbidity and mortality. This study aimed to investigate the prevalence of MDR A. baumannii perirectal colonization among adult patients upon admission to the intensive care unit (ICU) over a 5-year period and to identify risk factors and outcomes associated with colonization. A retrospective cohort analysis of patients admitted to the medical intensive care unit (MICU) and surgical intensive care unit (SICU) at the University of Maryland Medical Center from May 2005 to September 2009 was performed using perirectal surveillance cultures on admission. Poisson and logistic models were performed to identify associated risk factors and outcomes. Four percent of the cohort were positive for MDR A. baumannii at ICU admission. Among patients admitted to the MICU, those positive for MDR A. baumannii at admission were more likely to be older, to have received antibiotics before ICU admission, and to have shorter length of stay in the hospital prior to ICU admission. Among patients admitted to the SICU, those colonized were more likely to have at least one previous admission to our hospital. Patients positive for MDR A. baumannii at ICU admission were 15.2 times more likely to develop a subsequent positive clinical culture for A. baumannii and 1.4 times more likely to die during the current hospitalization. Risk factors associated with MDR A. baumannii colonization differ by ICU type. Colonization acts as a marker of disease severity and of risk of developing a subsequent Acinetobacter infection and of dying during hospitalization. Therefore, active surveillance could guide empirical antibiotic selection and inform infection control practices.